Preliminary study on the influence of willingness to communicate (WTC) among Malaysian pre-university students - Anna Lynn Abu Bakar; Suyansah Swanto; Wardatul Akmam Din; Romzi Ationg (Pusat Penataran Ilmu Bahasa, Universiti Malaysia Sabah, 2020)
The English language is seen as an important medium of communication between people especially in higher institutions in Malaysia and also in the working world. Thus, a lot of effort has been put in in producing students who are competent in communicating effectively in different social and professional context. This can be seen when the Ministry of Education has made a lot of changes in making sure that the syllabus is aligned with the CEFR and MIA requirements. This study looks into students’ willingness to communicate inside the classroom. This paper presents a preliminary discussion on the factors that influence students’ English oral competency among preuniversity students in University Malaysia Sabah (UMS), Sabah, Malaysia in relation to their Willingness to Communicate (WTC) in English.